2009
DOI: 10.1021/ci9002624
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Prediction for Orphan Targets Using Support Vector Machines and Various Target-Ligand Kernels Is Dominated by Nearest Neighbor Effects

Abstract: Support vector machine (SVM) calculations combining protein and small molecule information have been applied to identify ligands for simulated orphan targets (i.e., targets for which no ligands were available). The combination of protein and ligand information was facilitated through the design of target-ligand kernel functions that account for pairwise ligand and target similarity. The design and biological information content of such kernel functions was expected to play a major role for target-directed liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 35 publications
0
76
2
Order By: Relevance
“…[42] In a followup study, Wassermann, Geppert, and Bajorath examined the effect of ligands predicted for orphan targets in which closely related proteins of the target orphan had a set of ligands. [43] In such cases, they concluded that the ligands of the related proteins were more influential than particular optimizations of interaction prediction schemes. The result Special Issue Chemogenomics Table 1.…”
Section: Cpi Similarity Metrics and Examplesmentioning
confidence: 99%
“…[42] In a followup study, Wassermann, Geppert, and Bajorath examined the effect of ligands predicted for orphan targets in which closely related proteins of the target orphan had a set of ligands. [43] In such cases, they concluded that the ligands of the related proteins were more influential than particular optimizations of interaction prediction schemes. The result Special Issue Chemogenomics Table 1.…”
Section: Cpi Similarity Metrics and Examplesmentioning
confidence: 99%
“…the design of combined ligand-target kernels. A variety of kernel functions accounting for target sequence, structure or ontology information at different levels of sophistication have been combined with ligand similarity kernels to examine whether SVM LBVS performance might be further increased [17]. However, this was often not the case, revealing that compound similarity and nearest neighbor effects mostly dominated the recall rates of SVM calculations [17].…”
Section: Support Vector Machinesmentioning
confidence: 99%
“…A recent work form Bajorath and colleagues [99] suggests that simplified strategies for designing target-ligand kernels should be used since varying the complexity of the target kernel does not influence much the identification of ligands for virtually deorphanized targets. However, no true 3-D cavity descriptor has yet been reported as target kernel.…”
Section: Protein-ligand Fingerprintsmentioning
confidence: 99%